All‐trans retinoic acid regulates TGF‐β1‒induced extracellular matrix production via p38, JNK, and NF‐κB‒signaling pathways in nasal polyp‒derived fibroblasts. Issue 5 (27th February 2020) - Kim, Su‐Jong; Park, Joo‐Hoo; Lee, Seoung‐Ae; Lee, Jong‐Geun; Shin, Jae‐Min; Lee, Heung‐Man
Abstract : Background: All‐ trans retinoic acid (ATRA), a derivative of vitamin A, is known to have anti‐fibrogenic effects and regulates cell proliferation and differentiation. Therefore, these abilities of ATRA may influence tissue remodeling in the upper airway. The aims of the present study were to investigate the effects of ATRA on the myofibroblast differentiation, extracellular matrix (ECM) production, cell migration, and collagen gel contraction and to determine the molecular mechanisms of ATRA in TGF‐β1‐induced nasal polyp‒derived fibroblasts (NPDFs). Methods: NPDFs were isolated from nasal polyp. Cytotoxicity was evaluated by 3‐(4, 5‐dimethylthiazol‐2yl)‐2, 5‐diphenyl‐tetrazolium bromide assay. TGF‐β1‒induced fibroblasts were pretreated with ATRA. The expression levels of alpha‐smooth muscle actin (α‐SMA), collagen type 1, fibronectin, phospho‐mitogen‒activated protein kinase, and p‐p50 (nuclear factor‐kappaB [NF‐κB]) were measured by Western blot analysis, real‐time polymerase chain reaction, and/or immunofluorescence staining. Cell migration was analyzed with cell migration scratch assay and Transwell migration assay. Collagen contractile activity was measured using a collagen gel contraction assay. Results: ATRA had no significant cytotoxic effect in NPDFs. Expression levels of α‐SMA, collagen type 1, and fibronectin stimulated by TGF‐β1 were significantly downregulated in the ATRA‐pretreated fibroblasts. TGF‐β1‒induced cell migration and collagen gel contraction were significantly inhibited by ATRA pretreatment. ATRA also significantly inhibited phosphorylation of c‐Jun N‐terminal kinase (JNK), p38, and p50 in TGF‐β1‒induced NPDFs, but did not inhibit phosphorylation of extracellular signal‒related kinase (ERK). Conclusion: ATRA downregulated myofibroblast differentiation, ECM production, cell migration, and collagen gel contraction via p38, JNK‐dependent NF‐κB‒signaling pathways in TGF‐β1‒induced NPDFs. The findings suggest that ATRA could serve as a novel therapeutic agent to ameliorate nasal polyp development.